Estudos evolutivos no gênero Triportheus (Characiformes, Triportheidae) com enfoque na diferenciação do sistema de cromossomos sexuais ZZ/ZW - Yano, Cassia Fernanda (2016)
Triportheus genus (Characiformes, Triportheidae) presents a particular scenario 1 in fishes, with a ZZ/ZW sex chromosomes system for all species until now investigated. The Z chromosome is metacentric and the largest one of the karyotype, remaining morphologically conserved in all species. In contrast, the W chromosome differs in shape and size among species, from almost identical to markedly reduced in size in relation to the Z, with a clear heterochromatin accumulation associated with its differentiation process. This scenario in Triportheus, along with a well defined phylogeny for this group, provided an excellent opportunity to investigate the evolutionary events associated with the sex chromosomes differentiation, a matter of increasing interest to evolutionary biology in recent years. Therefore, the purpose of this study was to investigate the origin and differentiation of sex chromosomes in eight Triportheus species, using diverse conventional and molecular cytogenetics tools, such as C-banding, chromosomal mapping of rDNAs and several other repetitive DNA sequences, comparat ive genomic hybridization (CGH), microdissection of Z and W chromosomes and whole chromosome painting (WCP). The preferential accumulation of repetitive DNAs on the W chromosome highlighted the predominant participation of these sequences in the differentiation of this chromosome. Notably, the differential accumulation of microsatellites, and a hybridization pattern with no direct correlation to the ancestry of the W chromosome, put in evidence the particular evolutionary processes that shaped the sex-specific chromosome among species. The chromosomal mapping of 5S and 18S rDNAs and U2 DNAsn highlighted a very particular scenario in the distribution of these multigene families in Triportheus. Indeed, the variability in number of the rDNA sites on the autosomes, as well as the syntenic "status" of these three multigene families, showed their intense dynamism in the karyotype evolution, revealing a much more complex organization of these genes than previously supposed for closely related species. In addition, the occurrence of U2 DNAsn on the W chromosome of T. albus appears as an evolutionary novelty, while the occurrence of 18S rDNA in the Wq terminal region of all species pointed to a conserved condition for the genus, as well as a peculiarity in the evolutionary process of the W chromosome. Noteworthy, the use of WCP, and especially CGH experiments, put in evidence sequences which are shared by both Z and W chromosomes and sequences that are unique to each one. Thus, the Wq terminal region stood out with a high concentration of female specific sequences, in coincidence with the location of the 18S rDNA genes, allowing inferences about the origin of these cistrons on the sex-specific chromosome. Our data also showed that the ZZ/ZW system had, in fact, a common origin in Triportheus, considering the homologies found in chromosomal paintings using the Z and W probes. Triportheus auritus is the direct representative of the first lineage to differentiate in the genus and WCP experiments, using the Z chromosome probe of this species, have showed how this chromosome is notably conserved in all investigated species. On the other hand, the W chromosome showed variable patterns of homology among species, highlighting the molecular divergence emerged along its evolutionary history. In conclusion, the results obtained in this study allowed to certify the common origin of the ZZ/ZW sex system in Triportheus and to evaluate the intra- and inter-specific genomic homologies and differences between the sex pair, resulting in significant advances in the knowledge of the origin and differentiation of the sex chromosomes among lower vertebrates.